2012
DOI: 10.1371/journal.pone.0041017
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Activating EGFR Mutant Gene Contributes to Acquired Resistance to EGFR Tyrosine Kinase Inhibitors in Lung Cancer Cells

Abstract: Non-small-cell lung cancer harboring epidermal growth factor receptor (EGFR) mutations attains a meaningful response to EGFR-tyrosine kinase inhibitors (TKIs). However, acquired resistance to EGFR-TKIs could affect long-term outcome in almost all patients. To identify the potential mechanisms of resistance, we established cell lines resistant to EGFR-TKIs from the human lung cancer cell lines PC9 and11–18, which harbored activating EGFR mutations. One erlotinib-resistant cell line from PC9 and two erlotinib-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 39 publications
11
56
0
Order By: Relevance
“…5D and 6E). Similar to our findings, loss of addiction to mutant EGFR resulted in gain of addiction to both HER2/HER3 and PI3K/Akt signaling to acquire EGFR-TKI resistance (33).…”
Section: Discussionsupporting
confidence: 91%
“…5D and 6E). Similar to our findings, loss of addiction to mutant EGFR resulted in gain of addiction to both HER2/HER3 and PI3K/Akt signaling to acquire EGFR-TKI resistance (33).…”
Section: Discussionsupporting
confidence: 91%
“…Previously, we have reported the loss of PTEN expression with the loss of nuclear translocation of EGR-1, a transcription factor responsible for PTEN gene expression, in gefitinib-resistant clones (14)(15)(16). We also reported that either the complete or partial loss of the activated EGFR gene allele could also result in the acquisition of erlotinib resistance (17). In this present study, we further established erlotinib-resistant clones by step-wise selection following exposure to erlotinib and observed enhanced expression and activation of integrin b1 and Src.…”
Section: Introductionmentioning
confidence: 86%
“…After incubation for 72 hours, cytotoxicity was determined as described previously (17,18). Each value represents the average from triplicate wells AE SD.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…The most common form of lung cancer is non-small cell lung carcinoma (NSCLC), and, in a subset of these patients, tumor growth is driven by activating mutations in the epidermal growth factor receptor (EGFR). The most common activating mutations, accounting for 85% to 90% of all EGFR mutations, are the in-frame deletion in exon 19 (DelE746-A750) and the L858R point mutation in exon 21 (5,6). EGFR mutations occur in 10% to 15% of patients with NSCLC of Caucasian descent and 30% to 35% of patients with NSCLC of East Asian descent (5).…”
Section: Introductionmentioning
confidence: 99%